A comparison of risk and return for contract and independent hog finishing - J L Parcell; Michael R Langemeier (Kansas Agricultural Experiment Station Research Reports, 1995)
Risks associated with independent hog finishing have prompted producers to seek alternative production and marketing methods. A means of reducing risk has developed through contract hog finishing. Research results indicate that risk-neutral producers require contract base payments ranging from 11.25 to 14.00 per head. Strongly risk-averse producers require contract base payments ranging from 4.75 to 7.75 per head. The lower ends of the ranges are for a contract with performance incentives. The upper ends of the ranges are for a flat contract without performance incentives. Calculated required base payments are similar to those payments currently received by contract hog finishers.; Swine Day, Manhattan, KS, November 16, 1995
Keywords: Swine day; 1995; Kansas Agricultural Experiment Station contribution; no. 96-140-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 746; Swine; Risk management; Contract hog production